Treatment response to the RENEW weight loss intervention in schizophrenia: Impact of intervention setting - Brown, Catana (Schizophr Res, 2014)
BACKGROUND: Individuals with serious mental illness have high rates of obesity and a need for specialized weight loss intervention programs. This study examines the efficacy of the RENEW weight loss intervention and examines the impact of the intervention setting on outcomes. METHOD: 136 individuals with serious mental illness from 4 different settings were randomly assigned to receive the RENEW weight loss intervention or a control condition of treatment as usual. The RENEW intervention is a one year program that includes an intensive, maintenance and intermittent supports phase. RESULTS: The intervention group experienced a modest weight loss of 4.8 lbs at 3 months, 4.1 lbs at 6 months and a slight weight gain of 1.5 lbs at 12 months. The control group gained a total of 6.2 lbs at 12 months. However when settings were examined separately the responder sites had a weight loss of 9.4 lbs at 3 months, 10.9 lbs at 6 months and 7 lbs at 12 months. DISCUSSION: These results suggest that the settings in which individuals receive services may act as a support or hindrance toward response to weight loss interventions. The concept of the obesogenic environment deserves further examination as a factor in the success of weight loss programs.